2020
DOI: 10.3390/antiox9020171
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase 2 Mediates Myocardial Oxygen Wasting in Obesity

Abstract: Obesity and diabetes are independent risk factors for cardiovascular diseases, and they are associated with the development of a specific cardiomyopathy with elevated myocardial oxygen consumption (MVO2) and impaired cardiac efficiency. Although the pathophysiology of this cardiomyopathy is multifactorial and complex, reactive oxygen species (ROS) may play an important role. One of the major ROS-generating enzymes in the cardiomyocytes is nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2 (NOX2), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…In a previous study performed by our group, we demonstrated that ablation and pharmacological inhibition of NOX2 in obese mice improved the mechanical efficiency and reduced myocardial oxygen consumption (MVO 2 ) for non-mechanical cardiac work [ 23 ]. We have also previously demonstrated an association between increased ROS and increased MVO 2 [ 14 ], which together suggest a link between myocardial oxygen wasting and NOX2 activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study performed by our group, we demonstrated that ablation and pharmacological inhibition of NOX2 in obese mice improved the mechanical efficiency and reduced myocardial oxygen consumption (MVO 2 ) for non-mechanical cardiac work [ 23 ]. We have also previously demonstrated an association between increased ROS and increased MVO 2 [ 14 ], which together suggest a link between myocardial oxygen wasting and NOX2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several sources of ROS in cardiomyocytes, studies have confirmed that NADPH oxidase 2 (NOX2) is a crucial contributor to AngII-induced ROS production in the pathogenesis of heart failure [ 20 , 21 , 22 ]. We have previously found elevated myocardial ROS levels to be associated with increased myocardial oxygen consumption [ 14 ], and abrogation of NOX2 was shown to reduce cardiac ROS levels and improve cardiac efficiency in obesity-induced heart-failure [ 23 ]. Furthermore, non-pressor doses of AngII (50 ng/kg/min) have been shown to induce mitochondrial uncoupling in skeletal muscles [ 19 ], which could suggest an impact on mitochondrial efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Our present study also exhibited increased mitochondrial ROS production and NADPH oxidase (NOX) activity that generated ROS, and increased LPO in the pancreas and heart of GK diabetic rats. Studies have shown increased NOX activity to be associated with impaired calcium signaling and hyperglycemia-induced cardiomyocyte apoptosis and mitochondrial dysfunction, as well as the regulation of insulin secretion in pancreatic cells [ 36 , 37 , 56 ]. In addition to hyperglycemia, dyslipidemia has also been associated with NOX activation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Basic science studies implicate NOX2, NOX4, and NOX5 in the deterioration of diastolic function and adverse cardiac remodeling in response to pathological stimuli ( Table 2 ). A global loss of Nox2 limits myocardial ROS production and preserves diastolic function in response to diet-induced obesity [ 87 ], doxorubicin treatment [ 88 ], and myocardial infarction [ 89 ], and mitigates cardiac fibrosis in response to AngII, aldosterone, or pressure overload [ 41 , 90 , 91 , 92 ], whereas Nox2 overexpression in endothelial cells promotes cardiac fibrosis, inflammation, and diastolic dysfunction in response to AngII [ 93 ]. Inducible NOX2 activity in the heart in response to AngII appears to be particularly important for adverse cardiac remodeling and oxidative stress, as the loss of Nox2 protects from AngII-induced myocardial oxidative stress, hypertrophy, and fibrosis without altering AngII-induced hypertension [ 41 ].…”
Section: Nadph Oxidases In Cardiovascular Diseasementioning
confidence: 99%